Comparison of Academic Development in Catholic versus Non-Catholic Private Secondary Schools - Kim, Mikyong Minsun; Placier, Margaret (Education Policy Analysis Archives, 2004)
Utilizing hierarchical linear models, this study of 144 private schools (72 Catholic and 72 non-Catholic schools) drawn from the National Education Longitudinal Study of 1988 discovered that Catholic school students scored lower in reading than students at non-Catholic private schools. Analysis of internal school characteristics suggested that lower growth in reading achievement might be related in part to lower student morale in Catholic schools. However, we found no significant differences between Catholic and non-Catholic private secondary schools in the development of students' math, history/social studies, and science abilities from eighth to tenth grades. This study also identified important student- and school-level variables such as Catholicism, gender, risk factor, parental involvement, and enrollment size that help to explain the outcomes.